Home industry tape ketan sebagai penggerak perekembangan sosial ekonomi masyarakat desa Tarikolot (1980-2015) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
This study explains “Sticky-Rice Tapai Home Industry as the Drive of Community’s Socio-Economy of Tarikolot Village (1980-2015)”. It aims at describing the socio-economical aspects of the tapai homeindustries community in Tarikolot Village. It tries to comprehensively study their development from the early periods, the eagerness of the community towards tapai production, their process of change to develop the industries, and the impacts of the industries on the socioeconomical life of the community. The historical method comprises some stages that include data collection (heuristic), source critics, interpretation, and, finally, historiography stages. An interdisciplinary approach is then applied to intensify the analysis within the scopes of industrial, socio-economical transformation, and social mobility concepts. According to the result of the study, it is identified that Tarikolot Village has been central to tapai industries in Kuningan Regency that keep growing not only in terms of the number of industries but also in the number of productions. The development of the industries has contributed significantly to the transformations of the socio-economical life of the community, including the community’s life support, income, prosperity, and educational level.
Keywords: tapai; home industry; Tarikolot Village